Self-healing of damage inside metals triggered by electropulsing stimuli - Song, Hui (Sci Rep, 2017)
The microscopic defects that distributed randomly in metals are not only hard to detect, but also may inevitably cause catastrophic failure. Thus, autonomic probing and healing for damage inside metals continue to be a challenging. Here we show a novel approach for self-healing using electropulsing as a stimulus to trigger repairing of damaged metals. This is achieved via a process that through expelling absolutely currents, the microcrack causes them to be redistributed to form a concentrated and a diluted region around it, thereby inducing an extremely high temperature gradient and a large compressive stress, which drive material flow to close microcracks. Simultaneously, a large enough heat for bonding atoms was produced. That is, the microcrack as an empty cavity can be regarded as a special micro-device to shape a localized microscopic energy field, which in turn activates a healing process. The microstructure and mechanical property verified the extrinsic self-healing of a titanium alloy. The process is performed on a short timescale, is enable to detect automatically and act directly on the internal defects in metals, and to heal damage without any healing agent, long time heating as well as applied high pressure, offering unique advantages over conventional healing approaches.